Faktor-Faktor yang Berhubungan dengan Penggunaan Metode Kontrasepsi Tradisional - Wijayanti, Urip Tri (Jurnal Promosi Kesehatan Indonesia, 2021)
Background: The use of modern contraceptives in Central Java tends to decrease while traditional methods are increasing. The purpose of this study was to determine the factors associated with the use of traditional contraceptives among currently married women aged 15-49 in Central Java Province. The factors discussed include the number of children born alive, wife's age, wife's education, wife's occupation, residence, and access/utilization of family planning information sources.Method: The research design was cross-sectional, used secondary data from the Central Java SKAP 2019. The total number of respondents was 2.088 married women aged 15-49 years and not currently pregnant. Data collected by interview using a structured questionnaire. Data analysis with univariate analysis and bivariate analysis using the chi-square statistical test with a significance level of 5%.Results: The research found that most respondents were ≥ 35 years old, having ≥ 2 children, having high education level (senior high school to higher education), not working, living in the cities, and able to use some media to find information about family planning. The related factors to the use of traditional contraceptive methods were education and residences. The number of live birth children, ages, jobs, and the use of media did not influence the use of the traditional contraceptive method.